TRANSPORT TELECOMMUNICATION NETWORKS AS AN INFORMATION MEDIUM FOR OBTAINING INFORMATION RELEVANT TO CRIMINAL PROCEEDINGS: PROBLEMATIC ISSUES OF LEGAL REGULATION - Метелев , О. П. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2019)
Annotation. Scientific and technological progress, as well as the rapid development of information technologies, the formation of the information society, the introduction of telecommunications systems and networks into all vital processes, the availability of digital communications and information transmission have necessitated the use of new methods of combating crime in the new information (cybernetic) space, this artificially created environment, which is an integral part of transport telecommunications networks (TTN). The extraterritorial nature of transport telecommunication networks and systems, together with the global Internet, greatly complicates their legal regulation, as it is sometimes quite difficult to determine the jurisdiction of which state relates a criminal offense. Thus, when conducting silent investigative actions, a legitimate question arises as to the lawfulness of work in the information environment of the transport telecommunication network for obtaining digital evidence in the interests of criminal proceedings. Purpose of the article: to investigate the problematic issues of legal regulation when working in transport telecommunication networks in order to obtain information relevant to criminal proceedings during the conduct of silent investigative actions. The paper draws attention to the insufficient level of scientific research to cover the problematic issues of studying transport telecommunications networks as an information medium for legal obtaining digital evidence in the interests of criminal justice. The national legislation regulating public relations in this field is analyzed, as well as the case law of the European Court of Human Rights, which reveals some «white spots» in national legislation on ensuring the legitimacy and protection of human rights in the conduct of vague private communication interventions in the information environment of transport telecommunication networks. Taking into account the extraterritorial nature of the information (cyber) space, it is concluded that there is a need for clear legislative regulation of procedural activity in the transport telecommunication networks in order to ensure the security of the individual, society and the state as a whole in this sphere. The article also discusses different approaches to legal disparities in cyber crime investigations. The question of determining the crime scene in the information (cybernetic) space is raised, an attempt is made to define the «crime scene» and provides suggestions for improving legislation.

Анотація. Науково-технічний прогрес, а також стрімкий розвиток інформаційних технологій, формування інформаційного суспільства, впровадження телекомунікаційних систем та мереж в усі життєво важливі процеси, доступність засобів цифрового зв’язку та передачі інформації обумовило необхідність застосування нових методів боротьби зі злочинами в новому інформаційному (кібернетичному) просторі, цьому штучно створеному середовищі, невід’ємною складовою якого є транспортні телекомунікаційні мережі (ТТМ). Екстериторіальний характер транспортних телекомунікаційних мереж та систем разом із глобальною мережею Інтернет в значній мірі ускладнює їх правове регулювання, оскільки іноді досить складно визначити, до юрисдикції якої держави відноситься кримінальне правопорушення. Отже, при проведенні негласних розшукових (слідчих) дій виникає закономірне питання щодо правомірності роботи в інформаційному середовищі транспортної телекомунікаційної мережі для отримання цифрових доказів в інтересах кримінального провадження. Мета статті: дослідити проблемні питання правового регулювання при роботі в транспортних телекомунікаційних мережах для отримання відомостей значущих для кримінального провадження під час проведення негласних (слідчих) розшукових дій. У роботі звертається увага на недостатній рівень наукових досліджень у висвітленні проблемних питань вивчення транспортних телекомунікаційних мереж як інформаційного середовища для законного отримання цифрових доказів в інтересах кримінального судочин- ства. Аналізуються норми вітчизняного законодавства, які регулюють суспільні відносини в цій сфері, а також наводиться практика Європейського Суду з прав людини, яка викриває деякі «білі плями» в національних законодавствах щодо забезпечення законності та захисту прав людини під час проведення негласних заходів по втручанню у приватне спілкування в інформаційному середовищі транспортних телекомунікаційних мереж. З урахуванням екстериторіального характеру інформаційного (кібернетичного) простору робиться висновок щодо необхідності чіткого законодавчого регулювання процесуальної діяльності в транспортних телекомунікаційних мережах для забезпечення в цій сфері суспільних відносин безпеки особистості, суспільства і держави в цілому. У статті також розглядаються різні підходи щодо юридичних розбіжностей під час розслідувань злочинів у кіберпросторі. Ставиться питання щодо визначення місця злочину в інформаційному (кібернетичному) просторі, робиться спроба дати дефініцію «місця вчинення злочину» та надаються пропозиції щодо удосконалення законодавства.
ТРАНСПОРТНІ ТЕЛЕКОМУНІКАЦІЙНІ МЕРЕЖІ ЯК ІНФОРМАЦІЙНЕ СЕРЕДОВИЩЕ ДЛЯ ОТРИМАННЯ ВІДОМОСТЕЙ ЗНАЧУЩИХ ДЛЯ КРИМІНАЛЬНОГО ПРОВАДЖЕННЯ: ПРОБЛЕМНІ ПИТАННЯ ПРАВОВОГО РЕГУЛЮВАННЯ
Keywords: criminal process; transport telecommunication network; cyber space; crime scene.; кримінальний процес; транспортна телекомунікаційна мережа; кібернетичний простір; місце вчинення злочину.